The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1111/acps.12608
|View full text |Cite
|
Sign up to set email alerts
|

The economic costs of mental health‐related discrimination

Abstract: Objective To estimate and compare the economic costs of mental health‐related discrimination in the domains of health care, relationships and participation in leisure activities in England between 2011 and 2014. Method A subsample of the Viewpoint survey was interviewed using the Costs of Discrimination Assessment Questionnaire in 2011 and 2014. Information on the impact of discrimination on healthcare use, help seeking from family and friends and participation in leisure activities was recorded. Pattern of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…Further, WHPP emphasizing individual responsibility also lead to employees with overweight and obesity being targeted by stigma and discrimination. Both are associated with several unwarranted outcomes, such as decreased mental and physical health (Pascoe and Smart Richman, 2009 ; Puhl and Suh, 2015 ), increased healthcare costs (Osumili et al, 2016 ), and underperformance (Glover et al, 2017 ). Thus, if not implemented carefully, WHPP might have negative rather than the expected positive effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, WHPP emphasizing individual responsibility also lead to employees with overweight and obesity being targeted by stigma and discrimination. Both are associated with several unwarranted outcomes, such as decreased mental and physical health (Pascoe and Smart Richman, 2009 ; Puhl and Suh, 2015 ), increased healthcare costs (Osumili et al, 2016 ), and underperformance (Glover et al, 2017 ). Thus, if not implemented carefully, WHPP might have negative rather than the expected positive effects.…”
Section: Discussionmentioning
confidence: 99%
“…We propose and test that such framing of responsibility within WHPP forms a potent foundation for weight stigma and discrimination in the workplace. Since experiences of stigma are associated with decreased mental and physical health (e.g., Puhl and Suh, 2015 ) and with an associated increase in healthcare costs (e.g., Osumili et al, 2016 ), WHPP might form a cause of what they aim to cure. The current investigation tests the influence of both the presence and focus (individual vs. organizational responsibility) of WHPP on weight stigma and discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…The association is found for reduced productivity at work, for those who are employed, as well as impairment in other critical domains like parenting and other caretaker roles. Impairment due to discrimination would add to the economic costs of discrimination, such as increased health care costs (Evans-Lacko et al, 2014; Osumili et al, 2016), suggested by prior studies. Additional studies are needed to determine the extent to which these associations reflect causal relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Also using data from the Viewpoint survey, Osumili et al [12] found that individuals who reported experiences of discrimination in healthcare settings had higher costs of health service compared with those who did not. They also found that people who reported experiences of discrimination in relationships had higher healthcare costs than those who did not.…”
Section: Introductionmentioning
confidence: 99%